(untitled) (The Review of Diabetic Studies, 2025)
Background: Appendectomy remains the standard treatment for acute appendicitis, with laparoscopic appendectomy (LA) increasingly favored over open appendectomy (OA). However, debate persists regarding complication rates and outcomes, particularly in complicated appendicitis. Objective: To systematically review and synthesize evidence on the prevalence of postoperative complications following LA compared with OA, drawing on contemporary peer-reviewed literature. Methods: Following PRISMA 2020 guidelines, a systematic review was conducted across PubMed, Scopus, Web of Science, Embase, and Google Scholar. Eligible studies included randomized controlled trials, cohort studies, and meta-analyses published between 2000 and 2025, reporting complication prevalence after LA and/or OA. Outcomes of interest included surgical site infection, intra-abdominal abscess, operative time, hospital stay, and patient-reported measures. Quality assessment was performed using the Newcastle-Ottawa Scale and Cochrane Risk of Bias tool. Results: Twenty-four studies met the inclusion criteria. LA was consistently associated with lower wound infection rates, shorter hospitalization, and faster return to normal activities. Intra-abdominal abscess rates were occasionally higher in complicated appendicitis treated laparoscopically, though recent randomized trials and national database studies suggest comparable safety profiles. Operative time was generally longer for LA, but this difference diminished in more recent studies. Patient-centered outcomes such as pain, cosmesis, and satisfaction favored LA, with strong benefits observed in obese patients and other high-risk groups. Conclusion: LA demonstrates clear advantages over OA in terms of wound-related complications, recovery, and patient satisfaction, establishing it as the preferred approach for appendectomy. Caution remains warranted in complicated appendicitis, where intra-abdominal abscess risk should be considered, and in contexts where conversion to OA is necessary.